Oil-wet cement slurry system for oil and gas well cementing and preparation method thereof

By using an oil-philic-based cementing system in oil and gas well cementing, the problem of poor cementing quality between cement slurry and well walls is solved, and more efficient cementing of oil and gas wells is achieved, reducing cementing costs and improving single well recovery rate.

CN119735396APending Publication Date: 2025-04-01SINOPEC OILFIELD SERVICE CORPORATION +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411937469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the cementing of oil and gas wells constructed by oil-based drilling fluid, the cementing quality of cement slurry and well walls is poor, resulting in the residual oil film of the well wall, forming a sandwich layer, affecting the recovery rate of a single well.

Method used

A lipophilic-based cement slurry system is adopted, which consists of fresh water, oil well grade G cement, composite well wall reinforcement, retarder, anti-pollution agent, water loss-reducing agent and microsilicon powder. Through specific proportions and preparation methods, the cementing ability and anti-pollution properties of the cement slurry are enhanced.

Benefits of technology

The oleophilic-based cement slurry system can effectively wet and dissolve the oil film covered by the well wall, improve the quality of the interface cementation between the cement slurry and the well wall, reduce cementing costs, and improve single well recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an oleophilic cement slurry system for oil and gas well cementing and a preparation method thereof, wherein the raw materials are as follows: 100 parts of fresh water, 50-100 parts of oil well G grade cement, 15-20 parts of composite well wall strengthener, 1-3 parts of GH-9 retarder, 3-6 parts of KW-2 anti-pollution agent, 6-8 parts of G33S fluid loss reducer and 10-40 parts of microsilica powder; the retarder is first added to the fresh water and stirred and then allowed to stand; then the microsilica powder is slowly added under stirring, the oil well G grade cement is continuously added and stirred continuously, the fluid loss reducer is then added and stirred continuously, the anti-pollution agent is added under the stirring speed is increased, and the composite well wall strengthener is added and stirred and left to stand. The oleophilic cement slurry system can reverse the wetting of the oil film covered by the well wall, strengthen the bonding quality of the cement slurry and the well wall, thereby improving the cementing quality, and when the oleophilic cement slurry system is adopted, only a small amount of pre-flushing liquid is required to meet the cementing construction requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to oil and gas cementing, in particular to an oleophilic cement slurry system for oil and gas well cementing. The present invention also relates to a preparation method of the oleophilic cement slurry system for oil and gas well cementing, belonging to the technical field of oil and gas well cementing. Background Art

[0002] In recent years, with the continuous in-depth development of oil and gas exploration, unconventional oil and gas wells such as shale oil and shale gas have become the mainstream trend of oil and gas exploration and development. In order to reduce the frequency of underground complexities during the drilling of unconventional oil and gas wells, oil-based drilling fluids are widely used in the drilling process. The application of oil-based drilling fluids results in the well wall being completely covered with an oil film formed by the oil-based drilling fluid when drilling is completed. The oil film is difficult to remove after it is formed. At this stage, cementing construction can only use a large amount of pre-flushing fluid to clean the well wall for a long time to remove the oil film on the well wall and improve the bonding quality of cement slurry and the well wall. The use of a large amount of pre-flushing fluid to clean the oil film covering the well wall has the following three disadvantages:

[0003] 1. In order to improve the efficiency of cleaning the wellbore wall, the pre-flushing fluid has the characteristics of good fluidity and low density. In this case, when a large amount of pre-flushing fluid enters the annulus, the pressure of the annular liquid column will be reduced instantly, causing a large amount of formation fluid to invade the annulus, resulting in overflow, and in severe cases, it may lead to a blowout accident;

[0004] 2. The commonly used pre-flushing fluid on the market is a surfactant, which is very harmful to the oil and gas layer and easily pollutes the target layer of the oil and gas well, causing a decrease in the production of a single oil and gas well;

[0005] 3. The cost of pre-flushing fluid is relatively high. Using a large amount of pre-flushing fluid will inevitably increase the cementing cost of a single well and affect the cementing income of a single well. The pre-flushing fluid currently on the market removes the oil film by physical flushing, and the oil film removal efficiency is low.

[0006] When the oil film remains on the well wall, it will cause the traditional cement slurry to form a sandwich layer with the well wall, which will eventually lead to the deterioration of the bonding quality between the cement ring and the well wall, causing the interlayer crosstalk of the oil and gas wells, resulting in a decrease in the production of a single well, affecting the revenue of a single well, and in severe cases, it can cause the oil and gas well head to be pressurized, resulting in the interruption of oil and gas well production.

[0007] The Chinese invention patent with publication number CN 105670582B discloses a method for preparing a high-temperature resistant large temperature difference cement slurry for oilfield cementing. The large temperature difference resistance of the cement slurry system is very outstanding, but the application range is narrow, and it is only suitable for wellbore cementing operations constructed with water-based drilling fluids. For wellbore cementing operations constructed with oil-based drilling fluids, the original conventional cementing method still needs to be used to inject a large amount of oil displacement pre-fluid to clean the oil film remaining on the well wall for a long time. If the oil film is not cleaned thoroughly, the cement slurry invented in this patent does not have the ability to clean the oil film itself. In the later stage of the cement slurry bonding process with the well wall, a sandwich layer is easily formed, resulting in poor bonding quality of the cement ring formed by the cement slurry and the well wall, which ultimately leads to interlayer cross-talk between the production layers and affects the recovery rate of a single well.

[0008] In short, the poor bonding quality of cement slurry and well wall in the cementing construction of oil and gas wells constructed with oil-based drilling fluids has seriously affected the single well recovery rate of oil and gas wells. It is urgent to develop an oil-philic cement slurry system to solve the cementing problem of oil and gas wells constructed with oil-based drilling fluids. Summary of the invention

[0009] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification of this application and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0010] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0011] The primary purpose of the present invention is to overcome the problems existing in the prior art and provide an oleophilic cement slurry system for cementing oil and gas wells, which can reverse the wetting of the oil film covering the well wall and strengthen the bonding quality of the cement slurry and the well wall, thereby improving the cementing quality. When the oleophilic cement slurry system is used, only a small amount of pre-flushing fluid is required to meet the cementing construction requirements.

[0012] In order to solve the above technical problems, the oleophilic cement slurry system for oil and gas well cementing of the present invention has the following raw material components and weight contents: 100 parts of fresh water, 50-100 parts of oil well G grade cement, 15-20 parts of composite well wall strengthener, 1-3 parts of GH-9 retarder, 3-6 parts of KW-2 anti-pollution agent, 6-8 parts of G33S fluid loss reducer and 10-40 parts of microsilica powder.

[0013] Furthermore, the raw material components and their weight contents are as follows: 100 parts of fresh water, 50 parts of oil well G-grade cement, 15 parts of composite well wall strengthener, 1 part of GH-9 retarder, 3 parts of KW-2 anti-pollution agent, 6 parts of G33S fluid loss reducer and 10 parts of microsilica powder.

[0014] Furthermore, the raw material components and their weight contents are as follows: 100 parts of fresh water, 70 parts of oil well G-grade cement, 18 parts of composite well wall strengthener, 2 parts of GH-9 retarder, 4 parts of KW-2 anti-pollution agent, 7 parts of G33S fluid loss reducer and 25 parts of microsilica powder.

[0015] Furthermore, the raw material components and their weight contents are as follows: 100 parts of fresh water, 100 parts of oil well G-grade cement, 20 parts of composite well wall strengthener, 3 parts of GH-9 retarder, 6 parts of KW-2 anti-pollution agent, 8 parts of G33S fluid loss reducer and 40 parts of microsilica powder.

[0016] Furthermore, the preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0017] A1, preparing quaternary ammonium salt polymer;

[0018] A2. Preparation of hydrogen bond acceptors;

[0019] A3, preparing hydrogen bond donors;

[0020] A4, mixing the hydrogen bond acceptor and the hydrogen bond donor, stirring and heating to generate a deep eutectic solvent;

[0021] A5, mixing cyclodextrin and an organic hydrophobic monomer and grinding them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is (0.5-1):1;

[0022] A6. Add the hydrophobic monomer / cyclodextrin host-guest complex into a low eutectic solvent, add an initiator and heat under stirring, and obtain a composite well wall strengthener after cooling to room temperature.

[0023] Furthermore, the specific preparation process of the quaternary ammonium salt polymer in step A1 is as follows: first, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for more than 10 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, and the molar ratio of the quaternary ammonium salt monomer to the acrylic acid is 9:(1-6); potassium persulfate is used as an initiator to mix and stir the reaction at 70±3°C for 4-6 hours to generate a quaternary ammonium salt polymer.

[0024] Furthermore, in step A2: choline chloride or tetramethylammonium chloride or trimethylphenylammonium chloride is mixed and stirred with the quaternary ammonium salt polymer for more than 1 hour to generate a mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt as the hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% to 90% by weight.

[0025] Furthermore, in step A3: the small molecule alcohol and the macromolecular alcohol are mixed and stirred for more than half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as the hydrogen bond donor; the small molecule alcohol accounts for 70% to 90% wt of ethylene glycol and / or ethanol, and the macromolecular alcohol is polyvinyl alcohol.

[0026] Furthermore, in step A4: the mixture of the small molecule quaternary ammonium salt + the macromolecular quaternary ammonium salt and the mixture of the small molecule alcohol + the macromolecular alcohol are mixed and stirred at 70±3° C. for more than 40 minutes to generate the low eutectic solvent.

[0027] Further, in step A5: the organic hydrophobic monomer is styrene or butyl acrylate, and the cyclodextrin is α-cyclodextrin;

[0028] Or the organic hydrophobic monomer is N-naphthyl acrylamide, and the cyclodextrin is β-cyclodextrin.

[0029] Furthermore, in step A6: the mass of the hydrophobic monomer / cyclodextrin host-guest complex is 5-10% of the mass of the low eutectic solvent, and the initiator is potassium persulfate and its mass is 0.5% of the mass of the hydrophobic monomer; stirring at 60-80° C. for 4-6 hours, and constructing a composite well wall strengthener by in-situ synthesis in the low eutectic solvent mediated by cyclodextrin.

[0030] Further, the reaction process of generating the quaternary ammonium salt monomer is as follows:

[0031]

[0032] The polymerization process of the quaternary ammonium salt polymer is as follows:

[0033]

[0034] Further, the N-naphthyl acrylamide hydrophobic monomer is obtained by reacting acryloyl chloride with naphthylamine under ice bath conditions, and the process is as follows:

[0035]

[0036] Further, in step A6, the N-naphthyl acrylamide hydrophobic monomer / β-cyclodextrin host-guest complex is polymerized in a low eutectic solvent at 70±3° C. and stirred for 4 to 6 hours under the action of potassium persulfate initiator, and the generated hydrophobic polymer nanoparticles have the following molecular formula:

[0037]

[0038] Another object of the present invention is to overcome the problems existing in the prior art and provide a method for preparing an oleophilic cement slurry system for cementing oil and gas wells. The prepared oleophilic cement slurry has a wide applicable temperature range, adjustable density, good compatibility with cement slurry and drilling fluid, and can effectively dissolve the oil film after contacting the oil film on the well wall, thereby improving the interface bonding quality between the cement slurry and the well wall, and ultimately improving the cementing quality.

[0039] In order to solve the above technical problems, the preparation method of the oleophilic cement slurry system for oil and gas well cementing of the present invention comprises the following steps in sequence: S1, preparing raw materials: 100 parts of fresh water, 50-100 parts of oil well G grade cement, 15-20 parts of composite well wall strengthening agent, 1-3 parts of GH-9 retarder, 3-6 parts of KW-2 anti-pollution agent, 6-8 parts of G33S fluid loss reducer and 10-40 parts of microsilica powder;

[0040] S2. First, add the retarder into the fresh water and stir at 4000 rpm for 10 minutes, then let it stand for 30 minutes to allow it to fully hydrate and dilute;

[0041] S3. At a stirring speed of 4000 rpm, slowly add microsilica powder to the fresh water with retarder and continue stirring for more than 5 minutes, and then hydrate for 60 minutes;

[0042] S4. Continue to add oil well G grade cement at a stirring speed of 4000 rpm and continue stirring for more than 5 minutes;

[0043] S5. Continue to add the fluid loss reducer at a stirring speed of 4000 rpm and continue stirring for more than 10 minutes;

[0044] S6. Add the anti-pollution agent and continue stirring for 3 minutes at a stirring speed of 12000 rpm, and let it stand for 10 minutes to allow it to fully hydrate;

[0045] S7. Finally, add the composite well wall strengthening agent and stir for 2 minutes at a stirring speed of 12000 rpm, then adjust the stirring speed to 4000 rpm and continue stirring for 10 minutes, and let it rest for 10 minutes.

[0046] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. KW-2 anti-pollution agent is long-chain carboxylic acid ester polyoxyethylene-18, referred to as LMEO-18, which has an ester group and a double bond structure, similar to the structure of grease and wax, and has a strong dissolving and removing effect on grease. After the anti-pollution agent is added, its molecules will adhere to the cement molecules after hydration and dispersion. When the cement slurry contacts the oil film on the well wall, the oil film will be quickly dissolved by the long-chain carboxylic acid ester polyoxyethylene-18. The dissolved oil film molecules will flow freely inside the cement slurry, which can effectively reduce the friction between the molecules inside the cement slurry and effectively improve the rheological properties of the cement slurry.

[0047] 2. After the traditional cement slurry system comes into contact with the oil film remaining on the well wall, it cannot dissolve the oil film, causing the oil film to remain between the cement slurry and the well wall. As a result, the cement ring formed by the cement slurry is separated from the well wall by the oil film, forming a sandwich layer, which ultimately leads to the deterioration of the bonding quality of the cement ring.

[0048] 3. The density of the oleophilic cement slurry system of the present invention can be adjusted to 1.60-1.95 g / cm 3 , and the applicable temperature range is wide, 60-180°C. The lipophilic cement slurry system of the present invention has excellent anti-pollution performance. After mixing the oil-based drilling fluid: the lipophilic cement slurry of the present invention in a ratio of 3:1, at each target temperature and pressure of 60-180°C, its six-speed viscosity does not increase significantly, and the slurry still has good fluidity; after mixing the oil-based drilling fluid: the lipophilic cement slurry of the present invention in a ratio of 1:3, at each target temperature and pressure of 60-180°C, the thickening time does not shorten significantly, and the six-speed viscosity value does not increase significantly, which indicates that the thickening time of the lipophilic cement slurry is not shortened after contacting with the oil-based drilling fluid, indicating that it has excellent anti-pollution performance.

[0049] 4. The advantage of using macromolecules + small molecules as hydrogen bond donors and acceptors in composite well wall strengtheners is that small molecules have strong mobility and can be dispersed into the gaps between clay layers to prevent water molecules from penetrating; macromolecules have large molecular weights and long molecular chains that can glue clay together, enhancing its stability, and the hydrophobic groups in their structure can reduce the hydrophobicity of clay. At the same time, the hydroxyl groups and highly electronegative atoms in the structure of the low eutectic solvent can form hydrogen bonds with water molecules and aggregate solute molecules in the aqueous solution through hydrogen bonds to reduce water activity, thus better inhibiting the hydration of well wall clay and rock.

[0050] 5. Nanoparticles often have strong hardness and good high temperature resistance. However, single nanomaterials are often not easy to stay in microcracks during drilling and cannot play a good bridging role. The composite well wall strengthener introduces nanoparticles into the low eutectic solvent to make up for the defects of the low eutectic solvent and nanomaterials. During the oil field drilling process, the low eutectic solvent adheres to the pores of the well wall through electrostatic action and hydrogen bonding, thereby achieving effective plugging of microcracks, improving the plugging performance of drilling fluid, strengthening the well wall, avoiding the development of small cracks into large-size cracks, and preventing the well wall from becoming unstable.

[0051] 6. Most nanoparticles have hydrophobic properties and are difficult to dissolve and disperse well in polar low eutectic solvents. Therefore, nanoparticles usually cannot be directly reacted and generated stably in low eutectic solvents. The composite well wall strengthener introduces cyclodextrin molecules to mediate organic hydrophobic monomers such as styrene, acrylate, N-naphthyl acrylamide and cyclodextrin molecules to form a host / guest supramolecular complex. Since the outer edge of cyclodextrin is hydrophilic and the inner cavity is hydrophobic, it can provide a hydrophobic binding site like an enzyme, as a host to encapsulate various appropriate guests, such as organic molecules, inorganic ions and gas molecules. The large number of hydroxyl groups on its outer surface can also make it well dissolved and dispersed in polar solvents, so that it can be dissolved in polar low eutectic solvents, and then polymerized under the action of initiators to produce polymer nanoparticles. Through this polymerization reaction of nanoparticles mediated by cyclodextrin in low eutectic solvents, the preparation of low eutectic solvents, the preparation of nanoparticles and the compounding of the two can be completed in one step. The prepared nanoparticles have uniform size and good dispersion stability in the system, which is conducive to the good synergy between the nanoparticles and the low eutectic solvent, and plays a synergistic role in the drilling fluid system. DETAILED DESCRIPTION

[0052] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0054] Example 1

[0055] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0056] A1. Preparation of quaternary ammonium salt polymer

[0057] First, choline chloride and acryloyl chloride were mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer. The reaction process is as follows:

[0058]

[0059] The generated quaternary ammonium salt monomer is then copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to the acrylic acid is 9:1, potassium persulfate is used as an initiator, and the mixture is stirred and reacted at 67°C for 4 hours to generate a quaternary ammonium salt polymer. The polymerization process is as follows:

[0060]

[0061] A2. Preparation of Hydrogen Bond Acceptors

[0062] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% by weight.

[0063] A3. Preparation of hydrogen bond donors

[0064] Ethylene glycol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 70%wt.

[0065] A4. Preparation of deep eutectic solvent

[0066] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 67° C. for 40 minutes to generate a low eutectic solvent.

[0067] A5. Mix α-cyclodextrin and an organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.5:1.

[0068] A6. Adding a hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 5% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.5% of the mass of the organic hydrophobic monomer; stirring at 60° C. for 4 hours, and synthesizing the hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0069] The polymerization process of styrene is as follows:

[0070] After cooling to room temperature, a composite well wall strengthening agent is obtained.

[0071] Example 2

[0072] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0073] A1. Preparation of quaternary ammonium salt polymer

[0074] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 11 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:3, and potassium persulfate is used as an initiator to mix and stir at 70°C for 5 hours to generate a quaternary ammonium salt polymer.

[0075] A2. Preparation of Hydrogen Bond Acceptors

[0076] Tetramethylammonium chloride and quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80%wt.

[0077] A3. Preparation of hydrogen bond donors

[0078] The ethanol and polyvinyl alcohol were mixed and stirred for 35 minutes to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounted for 80% wt.

[0079] A4. Preparation of deep eutectic solvent

[0080] A mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt and a mixture of small molecule alcohol + large molecule alcohol are mixed and stirred at 70° C. for 40 minutes to generate a low eutectic solvent.

[0081] A5. Mix α-cyclodextrin and an organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.7:1.

[0082] A6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 7% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.7% of the mass of the organic hydrophobic monomer; stir at 70°C for 5 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and obtain a composite well wall strengthener after cooling to room temperature.

[0083] Example 3

[0084] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0085] A1. Preparation of quaternary ammonium salt polymer

[0086] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 11 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:6, and potassium persulfate is used as an initiator to mix and stir at 73°C for 6 hours to generate a quaternary ammonium salt polymer.

[0087] A2. Preparation of Hydrogen Bond Acceptors

[0088] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 90% by weight.

[0089] A3. Preparation of hydrogen bond donors

[0090] The ethanol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 90% by weight.

[0091] A4. Preparation of deep eutectic solvent

[0092] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 73° C. for 45 minutes to generate a low eutectic solvent.

[0093] A5. Mix α-cyclodextrin and an organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0094] A6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 10% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 1% of the mass of the organic hydrophobic monomer; stir at 80°C for 6 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and obtain a composite well wall strengthener after cooling to room temperature.

[0095] Example 4

[0096] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0097] A1. Preparation of quaternary ammonium salt polymer

[0098] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:4, and potassium persulfate is used as an initiator to mix and stir at 70°C for 5 hours to generate a quaternary ammonium salt polymer.

[0099] A2. Preparation of Hydrogen Bond Acceptors

[0100] The trimethylphenylammonium chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80% by weight.

[0101] A3. Preparation of hydrogen bond donors

[0102] Ethylene glycol and polyvinyl alcohol were mixed and stirred for 35 minutes to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounted for 80% wt.

[0103] A4. Preparation of deep eutectic solvent

[0104] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 70° C. for 45 minutes to generate a low eutectic solvent.

[0105] A5. β-cyclodextrin and an organic hydrophobic monomer N-naphthyl acrylamide are mixed and ground with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.8:1.

[0106] N-naphthyl acrylamide is obtained by reacting acryloyl chloride with naphthylamine in an ice bath, and the process is as follows:

[0107]

[0108] A6. Adding a hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 10% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.8% of the mass of the organic hydrophobic monomer; stirring at 80° C. for 6 hours, and synthesizing hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0109] The polymerization process of N-naphthyl acrylamide is as follows:

[0110] After cooling to room temperature, a composite well wall strengthening agent is obtained.

[0111] Example 5

[0112] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0113] A1. Preparation of quaternary ammonium salt polymer

[0114] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:5, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0115] A2. Preparation of Hydrogen Bond Acceptors

[0116] Tetramethylammonium chloride and quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 80%wt.

[0117] A3. Preparation of hydrogen bond donors

[0118] Ethylene glycol and polyvinyl alcohol are mixed and stirred for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 80%wt.

[0119] A4. Preparation of deep eutectic solvent

[0120] A mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt and a mixture of small molecule alcohol + large molecule alcohol are mixed and stirred at 70° C. for 40 minutes to generate a low eutectic solvent.

[0121] A5. Mix α-cyclodextrin and organic hydrophobic monomer butyl acrylate and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0122] A6. Adding a hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 8% of the mass of the low eutectic solvent; adding an initiator, potassium persulfate, under stirring, wherein the mass of the initiator is 0.8% of the mass of the organic hydrophobic monomer; stirring at 70° C. for 5 hours, and synthesizing hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin;

[0123] The polymerization process of butyl acrylate is as follows:

[0124] After cooling to room temperature, a composite well wall strengthening agent is obtained.

[0125] Example 6

[0126] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0127] A1. Preparation of quaternary ammonium salt polymer

[0128] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:2, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0129] A2. Preparation of Hydrogen Bond Acceptors

[0130] The choline chloride and the quaternary ammonium salt polymer are mixed and stirred for 1 hour to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% by weight.

[0131] A3. Preparation of hydrogen bond donors

[0132] Ethylene glycol and ethanol are mixed in a molar ratio of 1:1, and then mixed with polyvinyl alcohol for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 90%wt.

[0133] A4. Preparation of deep eutectic solvent

[0134] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 71° C. for 40 minutes to generate a low eutectic solvent.

[0135] A5. Mix α-cyclodextrin and an organic hydrophobic monomer styrene and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 0.9:1.

[0136] A6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 6% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.6% of the mass of the organic hydrophobic monomer; stir at 70°C for 5 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and obtain a composite well wall strengthener after cooling to room temperature.

[0137] Example 7

[0138] The preparation of the composite well wall strengthening agent comprises the following steps in sequence:

[0139] A1. Preparation of quaternary ammonium salt polymer

[0140] First, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for 10 minutes to generate a quaternary ammonium salt monomer; then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, the molar ratio of the quaternary ammonium salt monomer to acrylic acid is 9:5, and potassium persulfate is used as an initiator to mix and stir at 70°C for 6 hours to generate a quaternary ammonium salt polymer.

[0141] A2. Preparation of Hydrogen Bond Acceptors

[0142] The trimethylphenylammonium chloride and the quaternary ammonium salt polymer are mixed and stirred for 1.5 hours to generate a mixture of small molecule quaternary ammonium salt + large molecule quaternary ammonium salt as a hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 90% by weight.

[0143] A3. Preparation of hydrogen bond donors

[0144] Ethylene glycol and ethanol are mixed in a molar ratio of 1:1, and then mixed with polyvinyl alcohol for half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as a hydrogen bond donor, wherein the small molecule alcohol accounts for 80%wt.

[0145] A4. Preparation of deep eutectic solvent

[0146] The mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt and the mixture of small molecule alcohol + macromolecular alcohol are mixed and stirred at 70° C. for 45 minutes to generate a low eutectic solvent.

[0147] A5. Mix β-cyclodextrin and organic hydrophobic monomer N-naphthyl acrylamide and grind them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is 1:1.

[0148] A6. Add the hydrophobic monomer / cyclodextrin host-guest complex to a low eutectic solvent, wherein the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 9% of the mass of the low eutectic solvent; add initiator potassium persulfate under stirring, wherein the mass of the initiator is 0.9% of the mass of the organic hydrophobic monomer; stir at 80°C for 6 hours to synthesize hydrophobic polymer nanoparticles in situ in the low eutectic solvent mediated by cyclodextrin; and obtain a composite well wall strengthener after cooling to room temperature.

[0149] The performance tests of each embodiment are as follows:

[0150] 1. Shale rolling recovery test

[0151] Base slurry: 5% bentonite + 1% lignite resin SPNH, 5‰ sulfomethylphenolic resin type I SMP-1, 3‰ polyacrylate, 2‰ polyanionic cellulose PAC (600g bentonite + 12L clean water), about 1 part per ten thousand caustic soda can be added to adjust the pH value to 9, and sealed and cured at room temperature for 24 hours.

[0152] Comparative Example 1: The difference from the preparation method of Example 1 is that choline chloride and the synthetic quaternary ammonium salt polymer are mixed and stirred, with choline chloride accounting for 60%; ethylene glycol and polyvinyl alcohol are mixed and stirred, with ethylene glycol accounting for 60%.

[0153] Comparative Example 2: The difference from the preparation method of Example 1 is that: small molecule quaternary ammonium salt is mixed with large molecule quaternary ammonium salt, and the small molecule quaternary ammonium salt accounts for 95%; small molecule alcohol is mixed with large molecule alcohol, and the small molecule alcohol accounts for 95%.

[0154] Comparative Example 1, Comparative Example 2 and Examples 1 to 7 were added to the above base slurry to prepare a water-based drilling fluid for testing, with the addition ratio being 5%wt, the same below.

[0155] The test was conducted in accordance with Chapter 6 of the industry standard SY / T 5613-2016 "Test Methods for Physical and Chemical Properties of Shale by Drilling Fluids". The cuttings mass m1 before rolling is 50g, the screen residue mass m2 after rolling and the rolling recovery rate are shown in Table 1:

[0156] Table 1

[0157] sample <![CDATA[m2 / g]]> Rolling recovery rate (%) Base slurry 23.6 47.2 Comparative Example 1 40.03 80.06 Comparative Example 2 45.96 91.92 Example 1 47.38 94.76 Example 2 47.54 95.08 Example 3 49.02 98.04 Example 4 48.16 96.32 Example 5 47.85 95.7 Example 6 47.65 95.3 Example 7 48.41 96.82 .

[0158] Rolling recovery rate is an important indicator to measure the ability of drilling fluid to inhibit hydration and expansion of shale. During the drilling process, a high rolling recovery rate usually means that the drilling fluid can effectively inhibit the hydration and expansion of shale, thereby reducing the occurrence of complex situations such as wellbore collapse and drill sticking, and ensuring the smooth progress of drilling operations.

[0159] It can be seen from Table 1 that the low eutectic solvent has a great influence on the shale rolling recovery rate. The low eutectic solvent configured in the composite well wall strengthener is composed of a macromolecule plus a small molecule as a hydrogen bond donor and acceptor. The content of small molecules plays a major role in the shale rolling recovery rate, but if there are only small molecules to prevent water molecules from penetrating without the hydrophobic groups of large molecules, the effect will be reduced. The rolling recovery rates in the embodiments of the composite well wall strengthener have reached more than 94%, and the highest can reach 98.04%. However, after adjusting the small molecule content of Comparative Example 1 to 60%, its shale rolling recovery rate dropped greatly to only 80%. When the small molecule content of Comparative Example 2 is adjusted to 95%, it will still drop to 91%. However, compared with Comparative Example 1, it is still higher.

[0160] 2. Shale expansion rate test

[0161] The above-mentioned base slurry, comparative example 1 and comparative example 2 are still used.

[0162] The test was conducted in accordance with Chapter 5 of the industry standard SY / T 5613-2016 "Test Methods for Physical and Chemical Properties of Shale by Drilling Fluids". The test results after 2 hours and 16 hours are shown in Table 2:

[0163] Table 2

[0164] %(2h) %(16h) Base slurry 9.61 13.72 Comparative Example 1 5.88 11.4 Comparative Example 2 5.16 10.27 Example 1 3.92 7.31 Example 2 3.61 6.85 Example 3 2.32 4.55 Example 4 2.97 5.12 Example 5 3.02 5.54 Example 6 3.31 6.13 Example 7 2.67 4.87 .

[0165] The shale expansion rate is an important parameter to measure the volume expansion of shale after it comes into contact with water. It is of great significance for the exploration and development of oil and gas, as well as the design and optimization of drilling fluids. Generally speaking, a lower expansion rate means that the volume of shale changes less after it comes into contact with water, which may be beneficial to maintain the stability of the formation, reduce the complexity of the drilling process, and prevent well wall collapse or drill stuck.

[0166] It can be seen from Table 2 that the trends of shale expansion rate and shale rolling recovery rate are consistent. Both of them first improve with the increase of small molecule content. However, if there is no certain amount of macromolecular chain to cooperate, the performance will still decline if the content of small molecules is increased. In the example of the composite well wall strengthening agent, the shale expansion rate can reach 4.87% even after 16 hours. The small molecule content of comparative example 1 is the lowest, and the small molecule content of comparative example 2 is the highest. However, the shale expansion rates of both are not low, so the proportion of small molecules can only be within a certain range.

[0167] 3. Medium pressure filtration test

[0168] Base slurry is the same as before;

[0169] Comparative Example 3: The only difference between the preparation method of Example 1 and that of Example 1 is that the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 3% of the mass of the deep eutectic solvent.

[0170] Comparative Example 4: The only difference from the preparation method of Example 1 is that the mass of the hydrophobic monomer / cyclodextrin host-guest complex accounts for 13% of the mass of the deep eutectic solvent.

[0171] The samples before and after aging were subjected to medium-pressure filtration test. The sample aging was performed by rolling the sample for 10 hours at 120°C and then cooling it to room temperature. The test was performed in accordance with the "Filtration" chapter standard in API RP 13B-1 "Recommended Practice for Field Testing Water-based Drilling Fluids". The test results are shown in Table 3:

[0172] Table 3

[0173]

[0174] Medium pressure filtration loss is an important indicator of drilling fluid performance. It reflects the volume of drilling fluid passing through a specific filter paper under certain pressure and time conditions. It is usually used to evaluate the filtration characteristics of drilling fluid and the quality of mud cake formed. Generally speaking, the smaller the filtration loss of drilling fluid, the easier it is to form a low-permeability, flexible, thin and dense filter cake, which is beneficial to stabilize the well wall and protect the oil and gas layer.

[0175] It can be seen from Table 3 that the amount of medium pressure filtration loss is closely related to the proportion of nanoparticles in the low eutectic solvent. According to the experimental data, we can find that the effect of adding poly-N-naphthyl acrylamide nanoparticles is the best. The medium pressure filtration loss after aging is only 1.3ml and 1.4ml. On the other hand, adding too much or too little nanoparticles will have a bad effect on the medium pressure filtration loss, as shown in Comparative Examples 3 and 4, where the pressure filtration loss is 2.9ml and 3.9ml.

[0176] 4. Plugging performance test

[0177] The above-mentioned base slurry, comparative example 3 and comparative example 4 are still used.

[0178] By measuring the penetration depth of drilling fluid in the sand bed, the effectiveness of the plugging agent in plugging formation cracks and pores can be evaluated. The plugging properties of the base slurry and various drilling fluids were determined according to API specifications using a non-permeability tester (visual sand bed filter loss meter). The test method is as follows: Add sand with a particle size of 10 to 50 mesh to the cylinder of the visual sand bed filter loss meter, compact and flatten it to form a sand bed, then slowly add 500 mL of base slurry or drilling fluid to the cylinder, let it stand for 10 minutes, measure the depth of the base slurry or drilling fluid immersed in the sand bed, then gradually pressurize to 0.69 MPa, and measure the depth of the drilling fluid immersed in the sand bed after 10 minutes. The test results are shown in Table 4.

[0179] Table 4

[0180]

[0181] The results of the plugging performance test and the medium-pressure filtration performance test have the same trend, which is closely related to the proportion of nanoparticles in the drilling fluid. If the proportion of nanoparticles is too high, the results of the medium-pressure filtration test and the plugging performance test will only fluctuate within a certain range. Therefore, it is unnecessary to have too many nanoparticles in the drilling fluid, but the results are not ideal if the number of nanoparticles is small. Among the nanoparticles synthesized in a low eutectic solvent by the cyclodextrin-mediated composite well wall strengthener, the strength of its poly N-naphthyl acrylamide nanoparticles is the highest. The penetration depths of Example 4 and Example 7 after pressurization only reached 0.5 cm and 0.6 cm, but the data were not ideal after adding too many or too few nanoparticles, such as Comparative Example 3 and Comparative Example 4 reached 2.1 cm and 1.6 cm.

[0182] The raw materials used in the composite well wall strengthening agent are widely available and can be industrially produced. Meanwhile, the reagents used in the examples are all commercially available.

[0183] Example 8

[0184] The method for preparing an oleophilic cement slurry system for oil and gas well cementing comprises the following steps in sequence:

[0185] S1. Prepare raw materials: 100 parts of fresh water, 50 parts of oil well G grade cement, 15 parts of composite well wall strengthener, 1 part of GH-9 retarder, 3 parts of KW-2 anti-pollution agent, 6 parts of G33S fluid loss reducer and 10 parts of microsilica powder, wherein the composite well wall strengthener of Example 1 is used;

[0186] S2. First, add the retarder into the fresh water and stir at 4000 rpm for 10 minutes, then let it stand for 30 minutes to allow it to fully hydrate and dilute;

[0187] S3. At a stirring speed of 4000 rpm, slowly add microsilica powder to the fresh water with retarder and continue stirring for 5 minutes, and then hydrate for 60 minutes;

[0188] S4. Continue to add oil well G grade cement at a stirring speed of 4000 rpm and continue stirring for 5 minutes;

[0189] S5. Continue to add the fluid loss reducer and continue stirring for 10 minutes at a stirring speed of 4000 rpm;

[0190] S6. Add the anti-pollution agent and continue stirring for 3 minutes at a stirring speed of 12000 rpm, and let it stand for 10 minutes to allow it to fully hydrate;

[0191] S7. Finally, add the composite well wall strengthening agent and stir for 2 minutes at a stirring speed of 12000 rpm, then adjust the stirring speed to 4000 rpm and continue stirring for 10 minutes, and let it rest for 10 minutes.

[0192] Example 9

[0193] The method for preparing an oleophilic cement slurry system for oil and gas well cementing comprises the following steps in sequence:

[0194] S1. Prepare raw materials: 100 parts of fresh water, 70 parts of oil well G grade cement, 18 parts of composite well wall strengthener, 2 parts of GH-9 retarder, 4 parts of KW-2 anti-pollution agent, 7 parts of G33S fluid loss reducer and 25 parts of microsilica powder, wherein the composite well wall strengthener of Example 4 is used;

[0195] S2. First, add the retarder into the fresh water and stir at 4000 rpm for 10 minutes, then let it stand for 30 minutes to allow it to fully hydrate and dilute;

[0196] S3. At a stirring speed of 4000 rpm, slowly add microsilica powder to the fresh water with retarder and continue stirring for 6 minutes, and then hydrate for 60 minutes;

[0197] S4, at a stirring speed of 4000 rpm, continue to add oil well G grade cement and continue stirring for 8 minutes;

[0198] S5. Continue to add the fluid loss reducer and continue stirring for 12 minutes at a stirring speed of 4000 rpm;

[0199] S6. Add the anti-pollution agent and continue stirring for 3 minutes at a stirring speed of 12000 rpm, and let it stand for 10 minutes to allow it to fully hydrate;

[0200] S7. Finally, add the composite well wall strengthening agent and stir for 2 minutes at a stirring speed of 12000 rpm, then adjust the stirring speed to 4000 rpm and continue stirring for 10 minutes, and let it rest for 10 minutes.

[0201] Example 10

[0202] The method for preparing an oleophilic cement slurry system for oil and gas well cementing comprises the following steps in sequence:

[0203] S1. Prepare raw materials: 100 parts of fresh water, 100 parts of oil well G grade cement, 20 parts of composite well wall strengthener, 3 parts of GH-9 retarder, 6 parts of KW-2 anti-pollution agent, 8 parts of G33S fluid loss reducer and 40 parts of microsilica powder, wherein the composite well wall strengthener of Example 7 is used;

[0204] S2. First, add the retarder into the fresh water and stir at 4000 rpm for 10 minutes, then let it stand for 30 minutes to allow it to fully hydrate and dilute;

[0205] S3. At a stirring speed of 4000 rpm, slowly add microsilica powder to the fresh water with retarder and continue stirring for 8 minutes, and then hydrate for 60 minutes;

[0206] S4. Continue to add oil well G grade cement at a stirring speed of 4000 rpm and continue stirring for 10 minutes;

[0207] S5. Continue to add the fluid loss reducer and continue stirring for 15 minutes at a stirring speed of 4000 rpm;

[0208] S6. Add the anti-pollution agent and continue stirring for 3 minutes at a stirring speed of 12000 rpm, and let it stand for 10 minutes to allow it to fully hydrate;

[0209] S7. Finally, add the composite well wall strengthening agent and stir for 2 minutes at a stirring speed of 12000 rpm, then adjust the stirring speed to 4000 rpm and continue stirring for 10 minutes, and let it rest for 10 minutes.

[0210] The performance tests of the oleophilic cement slurry system for oil and gas well cementing of Examples 8 to 10 of the present invention and the conventional cement slurry system are compared as follows. The weight components of the conventional cement slurry system are: 100 parts of fresh water, 80 parts of oil well G grade cement, 2 parts of retarder, 6 parts of fluid loss reducer G33S, and 20 parts of microsilica powder.

[0211] 5. Sedimentation stability test

[0212] The temperature range of the bottom of unconventional oil and gas wells is 90-160°C. In order to fully promote the application of oleophilic cement slurry systems in unconventional oil and gas wells, the test temperature range of the present invention is 60-180°C. The sedimentation stability test is to determine whether the internal structure of the test sample is stable by measuring the density difference between the lower and upper parts of the cement stone module sample formed after the cement slurry is cured at a certain target temperature in a normal pressure curing box (≦90°C) or a pressurized curing kettle (>90°C) for 48 hours.

[0213] Test steps: ① Take a sample of the prepared cement slurry and then load it into the curing module; ② Put the module into a normal pressure curing box (≦90℃) or a pressurized curing kettle (>90℃), and set the temperature required for the test; ③ When the temperature of the curing kettle reaches the required temperature for the test, start the timer and take out the module after 48 hours; ④ Measure the density values ​​of the upper and lower parts of the module and calculate the density difference; ⑤ Compare the obtained density difference with the standard to determine whether the slurry sedimentation stability meets the standard. The test results are shown in Table 5:

[0214] Table 5

[0215] Maintenance conditions unit Example 8 Example 9 Example 10 Conventional cement slurry 60℃*48h <![CDATA[g / cm 3 ]]> 0 0 0 0.03 90℃*48h <![CDATA[g / cm 3 ]]> 0 0 0 0.06 120℃*48h <![CDATA[g / cm 3 ]]> 0.003 0.005 0.007 0.13 150℃*48h <![CDATA[g / cm 3 ]]> 0.004 0.006 0.009 0.31 180℃*48h <![CDATA[g / cm 3 ]]> 0.006 0.007 0.009 0.43

[0216] It can be seen from Table 5 that within the range of 60-180°C, the sedimentation stability of the oleophilic cement slurry systems of Examples 8 to 10 of the present invention are significantly better than that of the conventional cement slurry system.

[0217] 6. Anti-pollution performance test

[0218] The anti-pollution performance test is to measure the viscosity of the oil-based drilling fluid and cement slurry after mixing them in different proportions and leaving them to stand for a period of time under a certain temperature environment to judge the anti-pollution performance of the cement slurry.

[0219] Test steps: ① Take samples of the prepared cement slurry, mix them with the prepared oil-based drilling fluid in different proportions, and then put them into the pressurized thickener slurry cup (2 groups each); ② Put the slurry cup into the pressurized thickener and set the temperature and pressure required for the test; ③ After the temperature and pressure of the thickener reach the test target value, take out one group and test its six speeds on the six-speed viscosity instrument, and the other group continues to perform thickening experiments under the target temperature and pressure conditions; ④ If the thickening experiment continues on the thickener and it has not thickened for 10 hours, the experiment will be terminated manually and the slurry cup will be removed according to the process; if the viscosity reaches 100Bc at a certain time point within 10 hours, the slurry cup will be removed according to the process. The test results are shown in Tables 6 to 15:

[0220] Table 6

[0221]

[0222] Table 7

[0223] Mixing components Mixing ratio Experimental conditions Six-speed viscosity Thickening time Example 8: Oil-based drilling fluid 1:3 90℃*45MPa 153 / 90 / 63 / 33 / 6 / 3 600min not thick Example 9: Oil-based drilling fluid 1:3 90℃*45MPa 161 / 92 / 65 / 40 / 8 / 5 600min not thick Example 10: Oil-based drilling fluid 1:3 90℃*45MPa 165 / 94 / 70 / 43 / 9 / 6 600min not thick Conventional cement slurry: oil-based drilling fluid 1:3 90℃*45MPa 203 / 115 / 93 / 60 / 12 / 6 600min not thick

[0224] Table 8

[0225] Mixing components Mixing ratio Experimental conditions Six-speed viscosity Thickening time Example 8: Oil-based drilling fluid 1:3 120℃*60MPa 150 / 87 / 60 / 29 / 6 / 3 600min not thick Example 9: Oil-based drilling fluid 1:3 120℃*60MPa 158 / 90 / 63 / 36 / 7 / 4 600min not thick Example 10: Oil-based drilling fluid 1:3 120℃*60MPa 160 / 91 / 68 / 41 / 8 / 6 600min not thick Conventional cement slurry: oil-based drilling fluid 1:3 120℃*60MPa 196 / 111 / 89 / 59 / 11 / 7 600min not thick

[0226] Table 9

[0227]

[0228]

[0229] Table 10

[0230] Mixing components Mixing ratio Experimental conditions Six-speed viscosity Thickening time Example 8: Oil-based drilling fluid 1:3 180℃*90MPa 141 / 79 / 51 / 22 / 3 / 2 600min not thick Example 9: Oil-based drilling fluid 1:3 180℃*90MPa 144 / 81 / 56 / 28 / 5 / 3 600min not thick Example 10: Oil-based drilling fluid 1:3 180℃*90MPa 159 / 86 / 59 / 31 / 7 / 5 600min not thick Conventional cement slurry: oil-based drilling fluid 1:3 180℃*90MPa 189 / 101 / 77 / 50 / 10 / 6 600min not thick

[0231] Table 11

[0232] Mixing components Mixing ratio Experimental conditions Six-speed viscosity Thickening time Example 8: Oil-based drilling fluid 3:1 60℃*30MPa 171 / 118 / 93 / 68 / 10 / 6 533min Example 9: Oil-based drilling fluid 3:1 60℃*30MPa 175 / 119 / 96 / 71 / 11 / 7 556min Example 10: Oil-based drilling fluid 3:1 60℃*30MPa 177 / 119 / 99 / 74 / 12 / 7 583min Conventional cement slurry: oil-based drilling fluid 3:1 60℃*30MPa >300 / 217 / 160 / 93 / 14 / 8 415min

[0233] Table 12

[0234] Mixing components Mixing ratio Experimental conditions Six-speed viscosity Thickening time Example 8: Oil-based drilling fluid 3:1 90℃*45MPa 168 / 113 / 90 / 61 / 9 / 5 505min Example 9: Oil-based drilling fluid 3:1 90℃*45MPa 171 / 114 / 91 / 66 / 10 / 6 518min Example 10: Oil-based drilling fluid 3:1 90℃*45MPa 173 / 116 / 93 / 69 / 11 / 6 530min Conventional cement slurry: oil-based drilling fluid 3:1 90℃*45MPa >300 / 206 / 155 / 89 / 13 / 8 376min

[0235] Table 13

[0236]

[0237]

[0238] Table 14

[0239]

[0240] Table 15

[0241]

[0242] It can be seen from Tables 6 to 10 that within the range of 60 to 180° C., after the oleophilic cement slurry systems of Examples 8 to 10 of the present invention are mixed with the oil-based drilling fluid at a ratio of 1:3, at different temperatures tested in the pressurized thickener, although the thickening time is greater than 600 min, the six-speed viscosity of the conventional cement slurry system mixed with the oil-based drilling fluid has a significantly higher trend than that of the mixture of the oleophilic cement slurry and the oil-based drilling fluid, and the slurry is significantly thickened.

[0243] It can be seen from Tables 11 to 15 that after the lipophilic cement slurry systems of inventive Examples 8 to 10 were mixed with the oil-based drilling fluid at a ratio of 3:1, the thickening time did not show a significant shortening, and the six-speed viscosity value did not show a significant increase at different temperatures tested in the pressurized thickener. On the contrary, after the conventional cement slurry was mixed with the oil-based drilling fluid at a ratio of 3:1, the thickening time was significantly shortened, and the six-speed viscosity value increased due to the thickening of the slurry. By comparison, it was found that the invented Examples 8, 9, and 10 had excellent anti-pollution performance and met the needs of on-site construction.

[0244] If the filtration loss of cement slurry is too large (>50ml) under high temperature environment, firstly, the permeability of cement stone formed by the hydration reaction of cement slurry will increase, the compressive strength will decrease, and finally the cement ring bonding quality will be poor; secondly, in high permeability formations, excessive filtration loss will cause instantaneous thickening of cement slurry, resulting in cement slurry flash setting accidents; thirdly, a large amount of filtrate lost in low permeability formations will form water belts, causing the phenomenon of interlayer crosstalk in the sealing section, so it is particularly important to control the filtration loss of cement slurry. After the wellbore strengthener in the cement slurry system of the present invention is added, it can effectively promote the reaction process of the fluid loss reducer, strengthen the filtration loss reducing function of the fluid loss reducer, and achieve the effect of continuously reducing the filtration loss of cement slurry.

[0245] 7. Cement slurry filtration performance test

[0246] The filtration performance test of cement slurry refers to first stirring and curing the cement slurry in a normal pressure thickener or a pressurized thickener, and then using a static filtration tester to test the filtration performance. If the experimental temperature is greater than 90°C, the cement slurry is cured in a pressurized thickener at the target temperature for 20 minutes, and then the static filtration tester is used to test the filtration performance. If the experimental temperature is less than 90°C, the cement slurry is cured in a normal pressure thickener at the target temperature for 20 minutes, and then the static filtration tester is used to test the filtration performance.

[0247] Test steps: ① Pour the prepared cement slurry into a pressurized thickener (>90℃) or a normal pressure thickener (≦90℃) and stir for 20 minutes at the target temperature; ② Preheat the static filter loss instrument to the experimental target temperature; ③ After stirring, pour the cement slurry into the preheated static filter loss instrument, quickly connect the top valve and nitrogen pipeline, and place the measuring cylinder at the lower end of the outlet valve; ④ Apply and maintain a pressure of 7.0MPa on the filter loss cylinder and start the test; ⑤ Open the bottom valve, collect the filtrate and record the filtrate volume for 30 minutes. The filtrate volume for the test of 30 minutes should be recorded as "filtration loss". If "gas breakthrough" occurs before the test of 30 minutes, the filtration loss should be recorded as "calculated filtration loss". The filtration loss is calculated according to the following formula:

[0248]

[0249] V t —The volume of filtrate collected when “gas breakthrough” occurs, (ml);

[0250] t—time when “gas penetration” occurs, (min)

[0251] Table 16

[0252] Cement slurry system Experimental temperature Filtration loss (ml) Example 8 60℃ 26 Example 9 60℃ 23 Example 10 60℃ 20 Conventional cement slurry 60℃ 36

[0253] Table 17

[0254] Cement slurry system Experimental temperature Filtration loss (ml) Example 8 90℃ 31 Example 9 90℃ 28 Example 10 90℃ 26 Conventional cement slurry 90℃ 41

[0255] Table 18

[0256] Cement slurry system Experimental temperature Filtration loss (ml) Example 8 120℃ 36 Example 9 120℃ 32 Example 10 120℃ 28 Conventional cement slurry 120℃ 53

[0257] Table 19

[0258] Cement slurry system Experimental temperature Filtration loss (ml) Example 8 150℃ 39 Example 9 150℃ 36 Example 10 150℃ 30 Conventional cement slurry 150℃ 68

[0259] Table 20

[0260] Cement slurry system Experimental temperature Filtration loss (ml) Example 8 180℃ 41 Example 9 180℃ 38 Example 10 180℃ 33 Conventional cement slurry 180℃ 105

[0261] It can be seen from Tables 16 to 20 that, within the range of 60 to 180°C, the filtration loss of cement slurry in Examples 8 to 10 of the present invention is different at the same target temperature due to the different amounts of fluid loss reducer and wellbore reinforcement added. At the same target temperature, the amount of fluid loss reducer and wellbore reinforcement added increases, and the filtration loss of cement slurry gradually decreases. Under a high temperature environment of 180°C, the filtration loss corresponding to Examples 8 to 10 of the present invention is still less than 50 ml, indicating that Examples 8 to 10 of the present invention have excellent filtration loss reduction performance within the range of 60 to 180°C and meet the needs of on-site construction. By comparing conventional cement slurry with the cement slurry of the invention, it is found that when the temperature exceeds 120°C, the filtration loss of conventional cement slurry exceeds 50 ml. Under this condition, conventional cement slurry can no longer meet the needs of on-site construction.

[0262] The technical indicators of the main materials used in this cement slurry system are shown in Table 21:

[0263] Table 21

[0264]

[0265]

[0266] Products from other manufacturers that meet the above technical requirements may also be selected.

[0267] The above is only a preferred embodiment of the present invention, which shows and describes the basic principles, main features and advantages of the present invention, but does not limit the scope of patent protection of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. In addition to the above embodiments, the present invention may have other implementation modes without departing from the spirit and scope of the present invention. The present invention may also have various changes and improvements, and all technical solutions formed by equivalent substitution or equivalent transformation fall within the scope of protection required by the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents. The technical features not described in the present invention can be realized by or using existing technologies, which will not be repeated here.

Claims

1. An oleophilic cement slurry system for oil and gas well cementing, characterized in that: Its raw material components and weight contents are as follows: 100 parts of fresh water, 50-100 parts of oil well G grade cement, 15-20 parts of composite well wall strengthener, 1-3 parts of GH-9 retarder, 3-6 parts of KW-2 anti-pollution agent, 6-8 parts of G33S fluid loss reducer and 10-40 parts of microsilica powder.

2. The oleophilic cement slurry system for oil and gas well cementing according to claim 1, characterized in that: The raw material components and their weight contents are as follows: 100 parts of fresh water, 50 parts of oil well G grade cement, 15 parts of composite well wall strengthener, 1 part of GH-9 retarder, 3 parts of KW-2 anti-pollution agent, 6 parts of G33S fluid loss reducer and 10 parts of microsilica powder.

3. The oleophilic cement slurry system for oil and gas well cementing according to claim 1, characterized in that: The raw material components and their weight contents are as follows: 100 parts of fresh water, 70 parts of oil well G grade cement, 18 parts of composite well wall strengthener, 2 parts of GH-9 retarder, 4 parts of KW-2 anti-pollution agent, 7 parts of G33S fluid loss reducer and 25 parts of microsilica powder.

4. The oleophilic cement slurry system for oil and gas well cementing according to claim 1, characterized in that: The raw material components and their weight contents are as follows: 100 parts of fresh water, 100 parts of oil well G grade cement, 20 parts of composite well wall strengthener, 3 parts of GH-9 retarder, 6 parts of KW-2 anti-pollution agent, 8 parts of G33S fluid loss reducer and 40 parts of microsilica powder.

5. The oleophilic cement slurry system for oil and gas well cementing according to claim 1, characterized in that: The preparation of the composite well wall strengthening agent comprises the following steps in sequence: A1, preparing quaternary ammonium salt polymer; A2. Preparation of hydrogen bond acceptors; A3, preparing hydrogen bond donors; A4, mixing the hydrogen bond acceptor and the hydrogen bond donor, stirring and heating to generate a deep eutectic solvent; A5, mixing cyclodextrin and an organic hydrophobic monomer and grinding them with water to obtain a hydrophobic monomer / cyclodextrin host-guest complex, wherein the molar ratio of the organic hydrophobic monomer to the cyclodextrin is (0.5-1):1; A6. Add the hydrophobic monomer / cyclodextrin host-guest complex into a low eutectic solvent, add an initiator and heat under stirring, and obtain a composite well wall strengthener after cooling to room temperature.

6. The oleophilic cement slurry system for oil and gas well cementing according to claim 5, characterized in that: The specific preparation process of the quaternary ammonium salt polymer in step A1 is as follows: first, choline chloride and acryloyl chloride are mixed and stirred in an ice bath at a molar ratio of 1:1 for more than 10 minutes to generate a quaternary ammonium salt monomer, and then the generated quaternary ammonium salt monomer is copolymerized with acrylic acid, and the molar ratio of the quaternary ammonium salt monomer to the acrylic acid is 9:(1-6); potassium persulfate is used as an initiator, and the mixture is mixed and stirred at 70±3°C for 4-6 hours to generate a quaternary ammonium salt polymer.

7. The oleophilic cement slurry system for oil and gas well cementing according to claim 5, characterized in that: In step A2: choline chloride or tetramethylammonium chloride or trimethylphenylammonium chloride is mixed and stirred with the quaternary ammonium salt polymer for more than 1 hour to generate a mixture of small molecule quaternary ammonium salt + macromolecular quaternary ammonium salt as the hydrogen bond acceptor, wherein the small molecule quaternary ammonium salt accounts for 70% to 90% by weight.

8. The oleophilic cement slurry system for oil and gas well cementing according to claim 5, characterized in that: In step A3: the small molecule alcohol and the macromolecular alcohol are mixed and stirred for more than half an hour to generate a small molecule alcohol + macromolecular alcohol mixture as the hydrogen bond donor; the small molecule alcohol accounts for 70% to 90% wt of ethylene glycol and / or ethanol, and the macromolecular alcohol is polyvinyl alcohol.

9. The oleophilic cement slurry system for oil and gas well cementing according to claim 7, characterized in that: In step A4: the mixture of the small molecule quaternary ammonium salt + the macromolecular quaternary ammonium salt and the mixture of the small molecule alcohol + the macromolecular alcohol are mixed and stirred at 70±3° C. for more than 40 minutes to generate the low eutectic solvent.

10. The oleophilic cement slurry system for oil and gas well cementing according to claim 5, characterized in that: In step A5: the organic hydrophobic monomer is styrene or butyl acrylate, and the cyclodextrin is α-cyclodextrin; Or the organic hydrophobic monomer is N-naphthyl acrylamide, and the cyclodextrin is β-cyclodextrin.

11. The oleophilic cement slurry system for oil and gas well cementing according to claim 5, characterized in that: In step A6: the mass of the hydrophobic monomer / cyclodextrin host-guest complex is 5-10% of the mass of the low eutectic solvent, and the initiator is potassium persulfate and its mass is 0.5% of the mass of the hydrophobic monomer; stirring at 60-80° C. for 4-6 hours, and in situ synthesis and construction of a composite well wall strengthener in the low eutectic solvent mediated by cyclodextrin.

12. The oleophilic cement slurry system for oil and gas well cementing according to claim 6, characterized in that: The reaction process for generating quaternary ammonium salt monomer is as follows: The polymerization process of the quaternary ammonium salt polymer is as follows:

13. The oleophilic cement slurry system for oil and gas well cementing according to claim 10, characterized in that: The N-naphthyl acrylamide hydrophobic monomer is obtained by reacting acryloyl chloride with naphthylamine under ice bath conditions, and the process is as follows:

14. The oleophilic cement slurry system for oil and gas well cementing according to claim 10, characterized in that: In step A6, the N-naphthyl acrylamide hydrophobic monomer / β-cyclodextrin host-guest complex is polymerized in a low eutectic solvent at 70±3° C. with stirring for 4 to 6 hours under the action of potassium persulfate initiator, and the generated hydrophobic polymer nanoparticles have the following molecular formula:

15. A method for preparing an oleophilic cement slurry system for oil and gas well cementing, characterized in that: The method comprises the following steps in sequence: S1, preparing raw materials: 100 parts of fresh water, 50-100 parts of oil well G grade cement, 15-20 parts of composite well wall strengthening agent, 1-3 parts of GH-9 retarder, 3-6 parts of KW-2 anti-pollution agent, 6-8 parts of G33S fluid loss reducing agent and 10-40 parts of microsilica powder; S2. First, add the retarder into the fresh water and stir at 4000 rpm for 10 minutes, then let it stand for 30 minutes to allow it to fully hydrate and dilute; S3. At a stirring speed of 4000 rpm, slowly add microsilica powder to the fresh water with retarder and continue stirring for more than 5 minutes, and then hydrate for 60 minutes; S4. Continue to add oil well G grade cement at a stirring speed of 4000 rpm and continue stirring for more than 5 minutes; S5. Continue to add the fluid loss reducer at a stirring speed of 4000 rpm and continue stirring for more than 10 minutes; S6. Add the anti-pollution agent and continue stirring for 3 minutes at a stirring speed of 12000 rpm, and let it stand for 10 minutes to allow it to fully hydrate; S7. Finally, add the composite well wall strengthening agent and stir for 2 minutes at a stirring speed of 12000 rpm, then adjust the stirring speed to 4000 rpm and continue stirring for 10 minutes, and let it rest for 10 minutes.

Citation Information

Patent Citations

  • Preparation method of high temperature resistant large temperature difference cement slurry for oilfield cementing

    CN105670582B